Digital literacy among Sriwijaya University lecturers - Alamsyah Alamsyah (Universitas Negeri Yogyakarta, 2017)
This article aims to describe patterns of digital literacy among Sriwijaya University (SU) lecturer and its contribution to the implementation of eLearning. We used a mixed approach. Our population is 635 subjects who have been running and organizing through the e-learning plat-form of SU. We, then, selected 30 lecturers randomly as our samples. Data were collected through offline and online questionnaires, in-depth interviews, and secondary data collection. Likert Scale is used to measure digital literacy among respondents and e-learning implementation is explained using the SIMPLE model. We find that digital literacy competence among SU lecturers is in a high position. This situation is the initial capital for the implementation of e-learning at SU. However, this situation has not contributed to the implementation of e-learning because of (a) lecturer is not willing to adapt to the e-learning environment system; (b) policymakers have not been intervening several factors that contributed to e-learning implementation at the university level.Artikel ini bertujuan menggambarkan pola literasi digital di kalangan dosen Universitas Sriwijaya dan kontribusinya terhadap implementasi e-learning. Artikel ini berasal dari penelitian empiris yang menggunakan pendekatan campuran (kualitatif dan kuantitatif). Populasi penelitian adalah 365 mata kuliah yang telah dijalankan dan diorganisir dengan platform e-learning yang diadopsi Universitas Sriwijaya. Dari populasi ini, peneliti memilih 30 dosen secara acak sebagai sampel penelitian. Data dikumpulkan dengan menggunakan kuesioner online dan offline, wawancara mendalam, dan pengumpulan data sekunder. Skala Likert digunakan untuk mengukur tingkat literasi digital respondenpenelitian. Sedangkan implementasi e-learning dijelaskan dengan model SIMPEL. Kami menemukan bahwa tingkat literasi digital dosen Universitas Sriwijaya berada pada posisi yang tinggi. Situasi ini merupakan modal awal untuk mengimplementasikan e-learning di Universitas Sriwijaya. Tetapi, situasi ini belum berkontribusi terhadap implementasi e-learning karena (a) para dosen belum bersedia beradaptasi dengan lingkungan sistem e-learning; dan (b) para pembuat kebijakan belum mengintervensi beberapa faktor yang berkontribusi terhadap implementasi e-learning di level universitas.